Pembuatan alat pendeteksi dan pengusir monyet secara otomatis di areal pertanian Desa Sugie Kabupaten Karimun - Wahyu Fernando; Fardin Hasibuan; Muhammad Irsyam; Harry Kurniawan; Muhammad Lyan Syaputra; M Arif Delpero; Supriyadi Supriyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
An automatic monkey detection and repellent system based on a Convolutional Neural Network (CNN) and a Raspberry Pi was developed to address crop damage caused by monkeys in Sugie Village, Karimun district. The system uses a webcam to detect monkeys within a radius of up to 50 meters and emits gunshot sounds audible up to 200 meters to automatically repel them. Solar panels power the system because the area has access to electricity only at night. The implementation of this device yielded significant results, reducing crop damage from an average of 9 damaged plants per visit to only 3, equivalent to a 66.7% decrease. Additionally, the solar panels provided lighting for the agricultural area, improving security and accessibility at night by 100%. This technology offers an effective and efficient solution compared to manual methods, which require constant monitoring. The project leverages modern innovation relevant to local needs by integrating renewable energy with image-based detection technology. This project has the potential to be replicated in other regions facing similar issues, supporting food security and improving rural communities.